Humeral lengthening by Ilizarov technique due post neonatal septic arthritis: a case report - Pinheiro, Rosana; Vilaverde, Daniel; Reis, Mafalda; Choupina, Bárbara; Ferreira, Andreia; Rodrigues, Domingues; Santos, Mafalda; Carvalho, João Dores (International Journal of Research in Orthopaedics, 2025)
Septic arthritis is an acute infection that occurs more frequently in children, is monoarticular, and most frequently affects the knee and hip. The main long-term sequelae of shoulder septic arthritis is shortening of the humerus and deformity of the affected joint. Humeral lengthening, whether unilateral or bilateral, is a valid method that improves the outcome following arm shortening and deformity correction. We presented the case of a teenager with sequelae of septic arthritis of the shoulder. He had dysmetria of the upper limbs of 120 mm, with shortening of the left humerus and humeral head subluxation. He underwent humerus osteotomy and humeral lengthening according to the Ilizarov technique. Currently, he presents some dysmetria, but have normal mobility. Radiologically we achieved 80 mm lengthening and reduce the humeral head, which was initially dislocated. Diagnosis of neonatal septic arthritis requires a high index of clinical suspicion. Humeral lengthening in post-septic shortening with the application of Ilizarov fixator is an effective, safe, reliable method.